Adult Mouse Kidney Stem Cells Orchestrate the De Novo Assembly of a Nephron via Sirt2‐Modulated Canonical Wnt/β‐Catenin Signaling. Issue 15 (22nd March 2022) - Han, Xiaobin; Sun, Zhongjie
Abstract: Generation of kidney organoids using autologous kidney stem cells represents an attractive strategy for treating and potentially replacing the failing kidneys. However, whether adult mammalian kidney stem cells have regenerative capacity remains unknown. Here, previously unidentified adult kidney Sca1 + Oct4 + stem/progenitor cells are isolated. Interestingly, culturing these cells leads to generation of kidney‐like structures. First, the assembly of self‐organizing 3D kidney‐like structures is observed. These kidney organoids contain podocytes, proximal tubules, and endothelial cells that form networks of capillary loop‐like structures. Second, the differentiation of kidney stem cells into functionally mature tubules and self‐organizing kidney‐shaped structures in monolayer culture that selectively endocytoses dextran, is shown. Finally, the de novo generation of an entire self‐organizing nephron from monolayer cultures is observed. Mechanistically, it is demonstrated that Sirt2‐mediated canonical Wnt/ β ‐catenin signaling is critical for the development of kidney organoids. Thus, the first evidence is provided that the adult mouse kidney stem cells are capable of de novo generating kidney organoids. Abstract : This study demonstrates that stem cells reside in the adult mammalian kidneys. The finding provides the first evidence that adult mouse Sca1 + Oct4 + kidney stem cells are capable of de novo generating a nephron in vitro. Mechanistically, Sirt2‐mediated canonical Wnt/ β ‐catenin signaling is critical for the development of kidney organoids.